R1 changes in the human placenta at 3 T in response to a maternal oxygen challenge protocol. (March 2016) - Ingram, Emma; Hawkins, Lauren; Morris, David M.; Myers, Jenny; Sibley, Colin P.; Johnstone, Edward D.; Naish, Josephine H.
Abstract: Oxygen-enhanced MRI non-invasively monitors placental oxygenation in-vivo. This technique has been demonstrated at 1.5 Tesla (T) in healthy pregnancies. The aim of this study was to investigate whether findings are comparable at 3T. Nine pregnant volunteers underwent MRI at 3T. Scans obtained R1 (1/T1) measures from T1 maps under air, followed by a dynamic series breathing 100% oxygen. A statistically significant negative correlation was found between dR1 and gestation ( P  = 0.0008, r = −0.90, Pearson correlation test). The effect of the field strength was not significant within regression analysis. Placental Oxygen-Enhanced MRI at 3T gives comparable results to those previously obtained at 1.5T. Highlights: OE-MRI marker of in vivo changes in pO2. First use of OE-MRI at 3T in placenta. Negative correlation of dR1 and gestation at 3T. Comparable correlation to previous measures at 1.5T.